METHODS OF TEACHING YOUNG ATTACKERS A TEAM ATTACK TECHNIQUE (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
Studing to play handball technique is to find and assimilate technical processes driving expression of the players optimal opportunities and increase their effectiveness as structured driving current game. This research was conducted at the level of junior handball teams during a competitive year in which research subjects were in training a large percentage of technical exercises, assessed by control samples prepared by federation of specialized or domain experts. To assess the level of technical training and progress have passed control samples at the beginning and end of the research.